Moderate Hajj: Management of Hajj Manasik Guidance Based on Religious Moderation - Ade Marpudin; Iim Wasliman; Hanafiah Hanafiah; Nandang Koswara (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
The purpose of this study was to obtain an overview and analyze the application of management and its functions in the guidance of religious moderation-based Hajj rituals at KBIHU Khazanah Mandiri Depok and Ibnu Aqil Bogor. This study uses descriptive-qualitative methods and approaches and data collection techniques through interviews, observation, and documentation studies. The foundation of management theory is from Henry Fayol, the theory of religious moderation refers to the principle of wasathiyah from Yusuf Al Qardhawi, and the theory of independence from Steinberg. The study results show that the management functions from the planning, organizing, directing, coordinating, and controlling stages in the guidance of Hajj rituals in both KBIHU have generally been implemented but have yet to be optimal. Several weaknesses include religious moderation material, independence, competency standards for prospective pilgrims, assessment in guidance, and visual aids. The results of this study recommend that the management of Hajj ritual guidance at KBIHU continues to be developed and optimized in the form of an integrated Hajj ritual guidance model based on religious moderation and quality-oriented.